Strategi Pemasaran dalam Meningkatkan Citra Pondok Pesantren Tahfidzul Qur’an Darul Ulum Khulafaur Rosyidin Desa Baja Kuning - Dewi Permata Sari; Ahmad Fuadi; Muamar Al Qadri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the marketing strategy applied by Pondok Pesantren Tahfidzul Qur'an Darul Ulum Khulafaur Rosyidin in improving the image of the institution and attracting public interest in pesantren education. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was carried out descriptively qualitative, with data validity testing through credibility, transferability, dependability, and confirmability tests. The results showed that the marketing strategy is carried out through determining the target market tailored to the needs of the community, determining the competitive position with other institutions, as well as the marketing mix through social media promotions, brochures, superior religious activities, and active involvement of all school components including alumni. The implementation of this marketing strategy has proven effective in increasing the number of new students and forming a positive image of the institution. Excellent programs such as Tahfizhul Qur'an become the main attraction of the pesantren. Thus, a planned marketing strategy that involves all elements of the school is very important in increasing public trust in pesantren educational institutions.